Limited household risk sharing: General equilibrium implications for the term structure of interest rates - Indrajit Mitra; Yu Xu (Federal Reserve Bank of Atlanta, 2020)
We present a theory in which limited risk sharing of idiosyncratic labor income risk plays a key role in determining the dynamics of interest rates. Our production-based model relates the crosssectional distribution of labor income risk to observable aggregate labor market variables. Our model makes two key predictions. First, it predicts positive risk premia for long-term bonds while simultaneously matching key macroeconomic moments. Second, it predicts a negative correlation between current labor market conditions (as measured by labor market tightness or the job-finding rate) and future bond excess returns. We provide evidence for these predictions.
Keywords: E24; E43; E44; G12; J64; 330; interest rates; nondiversifiable labor income risk; labor market frictions; bond risk premia